ANALISIS PENGARUH NON PERFORMING LOAN, LOAN TO DEPOSIT RATIO, BIAYA OPERASIONAL TERHADAP PENDAPATAN OPERASIONAL TERHADAP KINERJA KEUANGAN PADA BANK UMUM SYARIAH - Bi Rahmani, Nur Ahmadi (Dinamika Akuntansi Keuangan dan Perbankan, 2022)
This study aims to determine and analyze the effect of non-performing loans (NPL), loan to deposit ratio (LDR), operational costs on operating income (BOPO) on financial performance at Islamic commercial banks for the period 2015 to 2020. The approach uses a quantitative approach with . The type of data used in this study is quantitative data sourced from secondary data. The data collection technique in this study used a documentation study. The data analysis used is multiple linear regression with the results of this study showing that the NPL of non-performing loans has an effect on the Financial Performance (ROA) of Islamic Commercial Banks in 2016 and 2020. The ratio of loans to deposits (LDR) has no effect on Financial Performance (ROA) in Islamic Commercial Banks in 2016 and 2020. Operational costs on operating income (BOPO) affect the Financial Performance (ROA) of Islamic Commercial Banks in 2016 and 2020. Simultaneously the influence of non-performing loans (NPL), loan to deposit ratio (LDR) ), operational costs on operating income (BOPO) affect the Financial Performance (ROA) of Islamic Commercial Banks in 2016 and 2020